PENGARUH KEPERCAYAAN KONSUMEN PADA MEREK TERHADAP LOYALITAS MEREK - Muhammad Rafiq (Fakultas Ekonomi Universitas Islam 45, 2009)
Trust in a brand is consumers* willingness to rely on the brand in the face of risks, hoping that the brand can give positive results for them. For the reason, it is important to give more attention to consumers* trust in a brand. The benefit of the trust is that marketers can retain the position in the competition and reduce the costs to get consumers. Marketers, therefore, must entrust a name or a symbol namely a brand to build relationship with consumers. Most probably, the consumers would not directly trust a brand because each consumer has consideration upon making a purchase. Thus, the marketers must trace and identify factors that influence or build consumers* trust Some factors that may influence consumers* trust in a brand can be categorized into three characteristics, namely brand characteristic, company characteristic, and consumer-brand characteristic. This research is a replication of the research by Lau and Lee (1999) stating that those three characteristics are antecedent of the trust in a brand. The aim of this research was to identify those three characteristics in building the trust in a brand and to identify the influence of the trust in a brand to loyalty. With multiple regression analysis method, it was found that brand characteristics that consist of brand reputation, brand predictability, and brand competence influence the trust in a brand. All company characteristics that consist of trust in the company, company reputation, and motives of the company, except company integrity, influence trust in a brand. Consumer-brand characteristics consisting of brand liking, brand experience, and brand satisfaction influence the trust in a brand, while the similarity of consumers* self-concept and brand personality and the peer support do not.